Current perspectives on the use of statins in the treatment of dyslipidaemic patients: focus on pitavastatin - Lale Tokgözoglu; José Luis Zamorano (BioExcel Publishing Ltd, 2020)
A meeting entitled 'Current Perspective on the Use of Statins in the Treatment of Dyslipidemic Patients' was held in Stresa, Italy, on 27-28th June 2019. The presentations covered the 2019 European Society of Cardiology (ESC)/European Atherosclerosis Society (EAS) guidelines on dyslipidaemia, with discussion about the importance of controlling low-density lipoprotein cholesterol (LDL-C) and the pharmacological opportunities to reach the novel lipid goals. The roles of statins to manage dyslipidaemia in patients with different cardiovascular risks were also discussed. In particular, the efficacy and safety of pitavastatin for the treatment of dyslipidaemia were reviewed, highlighting its further advantages beyond LDL-C reduction. Therefore, the impact of statins on the glycaemic profile was discussed in view of the null/lower effect of pitavastatin as compared with other statins, as well as the interaction profile with other drugs commonly used. This meeting report summarizes the main messages of the discussion with a special focus on pitavastatin, whose main features in different settings are described.